EDTA related Pseudothrombocytopenia (PTCP) Incidence and Resolution of Clinically Threatened Artifact - Erum Amir, Amtul Quddos Latif, Mohammad Anwar, Noshaba Rahat, Gulnaz Khalid, Rafia Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: EDTA related pseudothrombocytopenia (PTCP) is immune mediated, time and temperature dependent spurious low platelet counts commonly observed in laboratory practices, as an in vitro phenomenon. Microscopic evaluation of every sample is not possible due to immense workload hence PTCP is overlooked mostly due to immense work load .Vortex mixer is practically feasible tool often used in laboratories to obtain the accurate platelet counts of the suspected samples by using same EDTA anticoagulated samples. Aim: To evaluate the frequency of EDTA related pseudothrombocytopenia in OPD of tertiary care centre and analyze the vortexing for resolution of PTCP. Methodology: This was case control study conducted in clinical pathology department of JPMC in collaboration with ICU from November 2022 to January 2023. Total 3000 samples of CBC were analyzed. 150 patients with platelet count less than 150 l , with abnormal histograms and platelet clumps on smear were enrolled as cases of PTCP. 150 healthy individuals with match age and gender recruited as controls. Sample was subjected to vortex for 2 min at 3000rpm Samples were reanalyze ,clumps dissolution recheck by smear. Results : Prevalence of isolated thrombocytopenia was 33%, with 15% cases of EDTA related PTCP, platelet clumps seen in all PTCP cases on smear, 87% clumps were resolved completely with significantly increased platelet counts post vortexing with p value <0.05. Conclusion: Vortexing has proved as a promising, rapid and a cost effective method to deal with PTCP, save patient from needless investigations and invasive procedures. Keywords: Thrombocytopenia, Pseudothrombocytopenia, Ethylene diamine tetra acetic acid, Vortex, Platelet histograms,